Depairing critical currents and self-magnetic field effects in submicron YBa2Cu3O7–d microbridges and bicrystal junctions - Ivanov, Z.G.; Fogel, N.Ya.; Yuzephovich, O.I.; Stepantsov, E.A.; Tzalenchuk, A.Ya. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2004)
We report on depairing critical currents in submicron YBa2Cu3O7–d microbridges. A small-angle bicrystal grain boundary junction is used as a tool to study the entrance of vortices induced by a transport current and their influence on the I–V curves. The interplay between the depairing and the vortex motion determines a crossover in the temperature dependence of the critical current. The high entrance field of vortices in very narrow superconducting channels creates the possibility of carrying a critical current close to the depairing limit determined by the S–S’ –S nature of the small-angle grain boundary junction.